Towards a fully functional integrated photonic-electronic platform via a single SiGe growth step - Littlejohns, Callum G. (2016)
Silicon-germanium (Si1-xGex) has become a material of great interest to the photonics and electronics industries due to its numerous interesting properties including higher carrier mobilities than Si, a tuneable lattice constant, and a tuneable bandgap. In previous work, we have demonstrated the ability to form localised areas of single crystal, uniform composition SiGe-on-insulator. Here we present a method of simultaneously growing several areas of SiGe-on-insulator on a single wafer, with the ability to tune the composition of each localised SiGe area, whilst retaining a uniform composition in that area. We use a rapid melt growth technique that comprises of only a single Ge growth step and a single anneal step. This innovative method is key in working towards a fully integrated photonic-electronic platform, enabling the simultaneous growth of multiple compositions of device grade SiGe for electro-absorption optical modulators operating at a range of wavelengths, photodetectors, and bipolar transistors, on the same wafer. This is achieved by modifying the structural design of the SiGe strips, without the need to modify the growth conditions, and by using low cost, low thermal-budget methods.